(untitled) (Proceedings of Voronezh State University. Series: Geology, 2022)
Introduction: The Baikal Rift Zone is a complex tectonic structure. Therefore, many issues related to the stratigraphic boundaries of the Late Cenozoic sedimentary deposits are still debatable. For example, the Tankhoi and Anosov formations were identified mainly by the changes in the lithological and mineralogical composition of lacustrine-alluvial deposits in large river valleys. Their palynological studies have mostly been fragmentary. In order to determine and correlate the age of the sediments in the abovementioned formations, a number of wells were bored in the valley of the Barguzin river. The article presents palynological materials related to the sections of two wells which allowed the author to determine the age of the penetrated sediments with a high degree of reliability. Methodology and materials: We studied deposits from two wells (No. 531, 532) bored within the territory of the Dzhidinsky structural basin located within the territory of the Baikal Rift zone. 38 samples from these wells were processed and studied. The obtained data were used to build diagrams which show the stages of vegetation development characteristic of the Late Cenozoic. Results: The obtained spore-pollen spectra from the two wells were characterised by similar species compositions. Diagrams built for the wells included 4 palynozones and 2 subzones in two of them. A characteristic feature for both of the diagrams was that their lower parts were dominated by the pollen of angiosperm plants: beeches, walnuts, and Myrica pollen. Birch and alder pollen were among subdominants, while cladotypes included Engelhardita, Platycarya, and chestnut pollen. The upper part was dominated by the pollen of gymnosperms: mostly spruces and to a lesser extent pines. Subdominants were Podocarpus and Tsuga pollen. Also, palynocomplexes included the pollen of bald cypresses and firs. Nearly all samples contained insignificant quantities of the pollen of herbaceous species (up to 2-3% of the total composition). These included the following families: Ericaceae and Chenopodiaceae. Spores presented by 4 families: Polipodiaceae, Lycopodiaceae, Sfagnacea, and Osmundaceae were found in all of the samples. Conclusions: The obtained palynological data were compared with the materials of palynological studies of the stratotype sections in the Chita Region and the materials of the South-East Region. This allowed determining the age of the sediments penetrated by wells 531 and 532, which is within the following chronological periods: Upper Miocene – Transition Area – Lower Pliocene.